METHODOLOGICAL FRAMEWORK FOR DEVELOPING SKILLS FOR RECEPTION AND PRODUCTION OF SCIENTIFIC LINGUISTIC TEXTS - Khuzhamova Khusnora Diyor kizi (Innovate Conferences, 2025)
The modern development of the humanities places new demands on the level of training of specialists in the field of linguistics. One of the key aspects of a linguist's professional work is working with scientific texts, which involves two interrelated processes: reception (perception, understanding, and interpretation) and production (creation of one's own scientific texts). Without mastering these skills, full participation in scientific communication is impossible, making this area methodologically significant and relevant. In the context of globalization and the expansion of the international scientific community, mastering the skills of working with scientific texts is particularly valuable.
Keywords: interrelated processes; scientific communication